Fullerene nanosheets for surface-enhanced Raman spectroscopy - Linchangqing Yang; Yahui Li; Wei Liu; Junhao Zhang; Qinghong Kong; Guangcheng Xi (ChemPhysMater)
Most surface-enhanced Raman scattering (SERS) substrates are based on noble metals or transition metal semiconductors. Developing nonmetallic SERS substrates is of great significance for expanding the application scope of SERS substrate materials. In this study, ultrathin C60 nanosheets with two-dimensional structures were synthesized using CVD and used as SERS substrates. Owing to the combined effects of favorable factors such as the expanded specific surface area and matched interfacial charge transport paths, the substrate has a minimum detection limit of 10−11 for rhodamine 6G and a Raman enhancement factor of 107. In addition, the C60 nanosheets exhibited good stability and uniformity as SERS substrates.